Clinical analysis and quality of life survey of hemophilia B patients in the central and western regions of China - Wang, Wen; Xu, Li; Wu, Jingsheng; Liu, Weiyong; Jin, Jiao; Huang, Jing; Xu, Zhongjin; Huang, Yali; Li, Bai; Liu, Yufeng; Zhang, Qing; Zhou, Min; et al. (Frontiers in Pediatrics, 2024)
Objective: To study the current status of hemophilia B (HB) patients in the central and western regions of China.Methods: This cross-sectional, multicenter study was conducted in seven provinces in the central and western regions of China from April 2019 to June 2023. Samples were collected for the factor Ⅸ activity, inhibitor screen, and gene mutation. Furthermore, the status of six index joints and quality of life (QoL) were assessed.Results: A total of 185 HB patients (mild 15, moderate 75, and severe 95) with a mean age of 16.40 years were enrolled. 30.3% (56/185) of patients had a family history of HB. 34.6% (64/185) of HB patients had diagnostic delay and 38.5% (69/179) experienced treatment delay. The incidence of inhibitors was 6.1% (11/179). We identified 123 genetic variants in this study, with missense mutations being the most common. 84.0% (89/106) of HB mothers were genetically identified as carriers, with 27.7% (13/47) of carriers having clotting factor levels less than 0.40 IU/mL. 71.4% (132/185) of HB patients had a history of joint hemorrhage, with a rate of target joint in these patients was 64.4% (85/132). Lower extremity joints were most often affected in patients. The Hemophilia Joint Health Score (HJHS) score was significantly positively correlated with the Hemophilia Early Arthropathy Detection with Ultrasound in China (HEAD-US-C) (r = 0.542, P < 0.001). Patients who received prevention treatment, inhibitor negative, without treatment delay, and without high-intensity replacement therapy showed a higher total score of the short form-36 health survey (SF-36).Conclusions: One-third of HB patients had delay in diagnosis and treatment, and the incidence of inhibitors was 6.1%. Target joints were present in nearly half of HB patients. Missense was the main mutation type. 84.0% of mothers of HB patients in this study were found to be carriers. HEAD-US-C and HJHS can complement each other in the evaluation of joint status and give a valid basis for early clinical management. Early detection and preventive treatment, as well as reducing high-intensity replacement therapy and inhibitor generation, can effectively improve the QoL of patients.